Use of Religious Observance as a Meaningful Occupation in Occupational Therapy - Kelly Thompson; Bryan M. Gee; Sara Hartje (Scholarworks @ WMU, 2018)
Background: Research shows that religious and spiritual beliefs influence a person's health and quality of life. Studies have found that religious people are healthier and require less access to health services, and that clients want to have their religious and spiritual needs addressed as a part of their plan of care. Method: This study used a descriptive survey design to explore the attitudes and behaviors of occupational therapists concerning religious observance in clinical practice. The survey yielded 181 responses from a random sampling from members of the American Occupational Therapy Association. Results: The study found that while the majority of the respondents felt that religious observance was an important occupation, most rarely or never addressed religious observance in clinical practice due to reasons such as the work context and the sensitivity of the topic. Conclusion: The findings suggest that education programs should better prepare graduates to view religious observance through the lens of task analysis rather than as a discussion of religion and spirituality. Furthermore, the findings suggest a potential unmet need that should be explored through further research